2016
DOI: 10.1515/sjecr-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Livolin Forte Ameliorates Cadmium-Induced Kidney Injury in Wistar Rats

Abstract: Th e kidney, which is an integral part of the drug excretion system, was reported as one of the targets of cadmium toxicity. Early events of cadmium toxicity in the cell include a decrease in cell membrane fl uidity, breakdown of its integrity, and impairment of its repair mechanisms. Phosphatidylcholine and vitamin E have a marked fl uidizing eff ect on cellular membranes. We hypothesized that Livolin forte® (LIV) could attenuate kidney damage induced by cadmium in rats. Twenty-fi ve adult male Wistar rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The result of the present study indicates that the administration of Cd induces peroxidative injury in the liver, kidney and intestine of rats, which is mediated by the inhibition of SOD activity and increase in the level of lipid peroxidation (Table 2). This is consistent with findings of previous studies (Asagba et al, 2004;Asagba and Eriyamremu, 2007;Ding et al, 2013, Nazima et al, 2015Ayala et al, 2014;Akomolafe et al, 2016, Oyinloye et al, 2016. One of the mechanisms attributed for the inhibition of SOD by Cd is the displacement of essential metals such as copper and zinc from the enzyme (SOD) and the inhibition of SOD activity might lead to oxidative stress (Timbrell, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…The result of the present study indicates that the administration of Cd induces peroxidative injury in the liver, kidney and intestine of rats, which is mediated by the inhibition of SOD activity and increase in the level of lipid peroxidation (Table 2). This is consistent with findings of previous studies (Asagba et al, 2004;Asagba and Eriyamremu, 2007;Ding et al, 2013, Nazima et al, 2015Ayala et al, 2014;Akomolafe et al, 2016, Oyinloye et al, 2016. One of the mechanisms attributed for the inhibition of SOD by Cd is the displacement of essential metals such as copper and zinc from the enzyme (SOD) and the inhibition of SOD activity might lead to oxidative stress (Timbrell, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Cd can inhibit complex III of the mitochondrial electron transport chain [48]. The observed nephrotoxicity in this study was associated with glomerular degeneration which has been shown in rats exposed to Cd [49]. Furthermore, the lungs represent one of the main routes through which Cd enters the body [40].…”
Section: Discussionsupporting
confidence: 59%
“…In this study we observed that MDA was markedly increased in rats exposed to Cd, thus proposing an increased oxidative stress. Comparable information had already been reported (Akomolafe et al, 2016). Increased MDA level due to Cd exposure could be because of excessive free radicals formatted which do harm to biological macromolecules (Stohs et al, 2001).…”
Section: Effects On Oxidative Stress Markersmentioning
confidence: 72%
“…Cadmium decreased nutrient assimilation and retention through its immediate impact on the intestinal mucosal cells. Additionally, exposure to low levels of heavy metals may do harm to the glucocorticoid system (Akomolafe et al, 2016). The glucocorticoid hormones assume an indispensable part in glucose regulation except carbohydrate, lipid, and protein metabolism.…”
Section: Results and Discussion Body Weight Relative Organ-body Weightmentioning
confidence: 99%
See 1 more Smart Citation